PHEP Cafeteria Management System - Zainudin, Muhammad Hafiiz; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2025)
The existing manual system for cafeteria management, ordering and payments at Kafeteria PHEP, Universiti Tun Hussein Onn Malaysia, leads to inefficiencies such as long wait times, frequent order mistakes, and difficulties in managing stall rentals. This study focuses on designing a cafeteria management system using object-oriented principles, developing it as both a web-based and mobile-based application, and testing its functionality through user acceptance testing. The system was developed using the iterative model and includes features such as online ordering, real-time menu updates, online payment, and statistical report generation. The results show improved menu accuracy, reduced waiting times, and more efficient stall management processes. The system successfully enhances operational efficiency for customers, stall staff, and administrators, with potential for future enhancements, such as AI-driven analytics for predicting customer preferences and improving service delivery.